PENGARUH PEMBELAJARAN METODE ACCELERATED LEARNING TERHADAP HASIL BELAJAR SISWA KELAS XI IPA MAN I PALU PADA POKOK BAHASAN LAJU REAKSI - Nur Intan A. Sumarau; Suherman Suherman (Jurnal Akademika Kimia, 2013)
This research is an experimental study.The aim of this study is to determine the effect of using accelerated learning and conventional methods for the learning result of class XI IPA MAN I academic year 2012/2013.The hypothesis of this research is there are significant effect between accelerated learning method and the learning result of class XI in reaction rate subject. Researchers took two classes to be used as the sample, which consisted of class XI Science II as a control with conventional methods and class XI science I as an experiment class with Accelerated Learning methods.Based on the obtained result, average value of student with conventional methods (grade control) is 6.47, while the average value of students with accelerated learning method (experimental class) is 9.67. From the t-test,was obtained thitung = 1.808> ttable = 1.66.This shows Ho refused and H1 accepted, so it can be concluded that there is significant effect between accelerated learning method with the learning result of reaction rate subject, rather than using conventional learning method. Accelerated learning method gave higher learning result than using conventional method in reaction rate subject.